Effectiveness of a teaching unit on the willingness to consume insect-based food – An intervention study with adolescents from Germany - Szczepanski, Lena; Dupont, Jacqueline; Schade, Fenja; Hellberg, Henrike; Büscher, Milan; Fiebelkorn, Florian (Frontiers in Nutrition, 2022)
This study investigated the effect of a four-lesson teaching unit on "Entomophagy and Sustainability" on the willingness of adolescents in Germany to consume insect-based food (N = 114; MAge = 15.77 years; SDAge = 1.12 years; female = 58.8%). The main aim of the study was to test whether the teaching unit can induce (long-term) changes in selected nutritional-psychological factors (food disgust, food neophobia, food technology neophobia), attitudes, knowledge, and the willingness to consume insect-based food. For this purpose, a paper-pencil questionnaire was conducted immediately before (pre-test), immediately after (post-test), and approximately 6 weeks after (follow-up test) the teaching unit. Although significant changes in food disgust, food neophobia, food technology neophobia, attitudes, and knowledge were recorded, adolescents’ willingness to consume insect-based food was not increased. Attitudes were identified as the strongest predictor for adolescents’ willingness to consume, while knowledge was not a significant predictor. Conclusions and recommendations to increase the effectiveness of the teaching unit that can be applied to other educational interventions are provided.